2018
DOI: 10.1186/s12961-018-0289-x
|View full text |Cite
|
Sign up to set email alerts
|

Gaps and strategies in developing health research capacity: experience from the Nigeria Implementation Science Alliance

Abstract: BackgroundDespite being disproportionately burdened by preventable diseases than more advanced countries, low- and middle-income countries (LMICs) continue to trail behind other parts of the world in the number, quality and impact of scholarly activities by their health researchers. Our strategy at the Nigerian Implementation Science Alliance (NISA) is to utilise innovative platforms that catalyse collaboration, enhance communication between different stakeholders, and promote the uptake of evidence-based inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 17 publications
0
53
0
Order By: Relevance
“…However, it clearly demonstrates that CRs are a recognised method of communicating the experience of educational and clinical value to a wide community and that there are currently significant barriers to the dissemination of such knowledge from HRLS. These barriers include insufficient skills and experience in writing CRs, together with potential financial cost, as other studies have suggested [3][4][5][6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it clearly demonstrates that CRs are a recognised method of communicating the experience of educational and clinical value to a wide community and that there are currently significant barriers to the dissemination of such knowledge from HRLS. These barriers include insufficient skills and experience in writing CRs, together with potential financial cost, as other studies have suggested [3][4][5][6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…In 2004-2006, a series of articles took a closer look at this gap and suggested that second-and third-world authors fear rejection, have insufficient writing skills, and overall lack incentive to engage in science [2][3][4][5][6]. Since then, other studies have shown also that scientists from developing countries are poorly represented on editorial boards of prestigious journals and that there is a higher peer rejection rate for papers submitted by authors in middle-and low-income countries [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the field of implementation science has emerged to promote and accelerate the systematic uptake of EBPs into community service settings to optimize public health impact [16]. Implementation science is a rapidly growing field as evidenced by multiple investigations of large-scale implementation efforts happening in the United States [17], Europe [18], Africa [19,20], and Latin America [21]. Several implementation models and frameworks have been developed to describe, guide, and evaluate implementation efforts [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The Nigeria Implementation Science Alliance (NISA) was established in 2015 as a robust partnership of 20 organizations that includes academic and non-governmental organizations, clinical service providers, and policy makers involved in HIV care in Nigeria (26). NISA is aimed at facilitating collaboration among partners, bridging research-to-practice gaps through application of implementation science approaches and implementation research in Nigeria and other countries in Sub-Saharan Africa, and identifying feasible and culturally appropriate strategies for improving public health through research (26,27). Yearly, NISA conferences have focused on "Prevention of mother to child HIV transmission(PMTCT)" (2015), "HIV/AIDS and related infections, adolescents health, STI & Hepatitis B" (2016), "Improving Health through Implementation Science & Research" (2017) and "Evidence-based approaches to enhance quality of care" (2018) (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%